(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to investigate if external rotation of the shoulder affects the deltoid in abduction exercise. Seven healthy men with experience in resistance training were evaluated in muscles anterior deltoid (AD) and posterior deltoid (PD) by surface electromyography. The subjects performed shoulder abduction to 90° in the frontal plane with elbow extension, with and without external rotation of the shoulder. All individuals performing the movement with the same load (one halter 8kg) right shoulder was used to obtain the data. Were used bipolar surface electrodes (distance 20 mm) and the data recorded by Miotool 400®. The electrodes were placed on the AD and PD and the ground reference electrode was placed on the spine of the 7th cervical vertebra. After raw data acquisition a bandpass filter (20-450 Hz) was applied and the values of Root Mean Square (RMS) were used for statistical analysis. The T-test showed significant differences in muscle AD with and without rotation and PD as well. greater activation of DA during shoulder abduction were also reported by several studies. CA and PA showed less activation in external rotation (35% and 17 %) respectively. This probably happened because rotator cuff acts as an antagonist of the deltoid muscle and may become less effective AD and PD by reciprocal inhibition. The external rotation would increase the distance between the origin and insertion of DA and decreasing distance between the origin and insertion of PD. We concluded that for AD and PD muscles exercise abduction without rotation of the shoulder would be the best to optimize these muscles.